Delivery of Floxuridine derivatives to cancer cells by water-soluble organometallic cages - Yi, Jeong Wu; Barry, Nicolas P. E.; Furrer, Mona A.; Zava, Olivier; Dyson, Paul J.; Therrien, Bruno; Kim, Byeang Hyean (My University, 2012)
Ruthenium water-sol. organometallic cage compds., assembled by 1,2,4,5-benzenetetrolato (dobq), 1,4,5,8-naphthalenetetrolato (donq) and 2,4,6-tri-4-pyridyl-1,3,5-triazine (tpt) ligands gave carceplex inclusion compds. I and II (L = ?6-cymene), resp., with amino acids and nucleoside antitumor agent, Floxuridine (2'-deoxy-5-fluorouridine) pyrene conjugates [R = (CH2)3CONHCHYCO2-5'-O-Floxuridine; Y = H, CH2Ph; R = (CH2)3CO2-5'-O-Floxuridine]. The self-assembly of tpt triangular panels with areneruthenium building blocks [(?6-p-cymene)RuCl]2Q (Q = dobq, donq) in the presence of a pyrenyl-nucleoside derivs. (1-R-pyrene), affords the triangular prismatic host-guest compds. I and II [(pyrene-R)?1]6+ and [(pyrene-R)?2]6+, resp. The inclusion of six monosubstituted pyrenyl-nucleosides [1-R-pyrene; R = R1-R6, where R1 = (CH2)3CO2-5'-O-2'-deoxyuridine, R2 = (CH2)3CO2-5-fluoro-5'-O-2'-deoxyuridine, R3 = (CH2)3CONHCH2CO2-5'-O-2'-deoxyuridine, R4 = (CH2)3CONHCH2CO2-5-fluoro-5'-O-2'-deoxyuridine, R5 = (CH2)3CONHCH(CH2Ph)2CO2-5'-O-2'-deoxyuridine, R6 = (CH2)3CONHCH(CH2Ph)CO2-5-fluoro-5'-O-2'-deoxyuridine] has been accomplished. The carceplex nature of [(pyrene-R)?1]6+ with the pyrenyl moiety firmly encapsulated in the hydrophobic cavity of the cage with the nucleoside groups pointing outward was confirmed by NMR spectroscopy and electrospray ionization mass spectrometry (ESI-MS), while the host-guest nature of [(pyrene-R)?2]6+ was studied in soln. by NMR techniques. In contrast to the floxuridine compds. used in the clinic, the host-guest complexes are highly water-sol. Consequently, the cytotoxicities of these water-sol. compds. have been established using human ovarian A2780 and A2780cisR cancer cells. All the host-guest systems are more cytotoxic than the empty cages alone ([1][CF3SO3]6, IC50 = 23 ?M; [2][CF3SO3]6, IC50 = 10 ?M), the most active compd. [1-R4-pyrene?1][CF3SO3]6 being 2 orders of magnitude more cytotoxic (IC50 = 0.3 ?M) on these human ovarian cancer cell lines (A2780 and A2780cisR). [on SciFinder(R)]
Keywords: ruthenium arene water soluble cage compd prepn self assembly; tripyridyl triazine dioxybenzoquinone dioxynaphthoquinone bridged ruthenium cymene complex prepn; inclusion antitumor nucleoside conjugate ruthenium organometallic hydrophilic cage; drug delivery antitumor nucleoside inclusion ruthenium organometallic hydrophilic cage